MAKNA HIJRAH BAGI KALANGAN REMAJA NON SANTRI: DAMPAK PENGGUNAAN MEDIA SOSIAL - Alif Alfi Syahrin; Bunga Mustika (LP2M IAIN Palangka Raya, 2020)
Various kinds of religious contents were widely circulated in social media with various kinds of covers to attract users, especially the millennial generation as active users of social media. Especially for non-santri teenagers who had a high curiosity in religious insight. The method used was a qualitative research with descriptive research. Data collection techniques used were non-participant observation, in-depth interviews and documentation. The informants in this study were Muslim teenagers who were still studying. The findings indicated that their favorite social media were Instagram, What’s up, and YouTube. The impact of utilizing social media was to add religious insight to Muslim adolescents who were obtained the materials before and the obstacles faced by adolescents when deciding to ‘hijrah ‘; that was, there were acts of bullying and were considered to only follow trends. The conclusion was the use of social media among non-santri teenagers is one way to answer curiosity about religious insight. Therefore, they realized new understanding in the form of ‘hijrah’. This condition was increasingly supported by the widespread of contents in social media and the presence of routine religious teachings in various mosques considered to represent the meaning of ‘hijrah’.